Assessment of ESDD on high-voltage insulators using artificial neural network - Ahmad A.S.; Ghosh P.S.; Shahnawaz Ahmed S.; Aljunid S.A.K. (2023)
The environmental and weather conditions cause flashover on polluted insulators leading to outages in a power system. It is generally recognized that the main causes leading to the contamination of insulators are marine pollution as found in the immediate neighborhood of the coastal regions, and solid pollution as found in the dense industrial areas. This research is directed towards the study of contamination of insulator under marine pollution. The effects of various meteorological factors on the pollution severity have been investigated thoroughly. A new approach using ANN as a function estimator has been developed and used to model accurately the relationship between ESDD with temperature (T), humidity (H), pressure (P), rainfall (R), and wind velocity (WV). The ANN-predicted ESDDs have been compared with the measured ones for a practical system. 2004 Elsevier B.V. All rights reserved.